Correlation Between Shear Wave Velocity and Liquefaction Resistance For Sandy Soils With A Shearing History Using Cyclic Tri-Axial Tests - G. J. Liu; N. Yasufuku; R. Ishikura (Lowland Technology International, 2019)
Abstrac